Efeitos da violência física contra a mulher no mercado de trabalho no Brasil em 2019 - Lima, Debora Anson (2023)
The aim of this study is to analyze the effects of physical violence against women on the outcomes of the Brazilian labor market. To do so, the Oaxaca-Blinder decomposition method is employed using data from the 2019 National Health Survey to examine the occurrence of different wage gaps between women who have not been exposed to physical violence and those who have. Additionally, the Recentered Influence Function tool is utilized to generalize this decomposition at any point in the labor income distribution. The results reveal that, in all the analyzed quartiles, there exists a wage advantage for the group of non-abused women over the abused group, with the advantage being more pronounced at higher income levels. This may suggest that in the lower quartiles, the effects generated by various deprivations to which women are subjected prevent the effects of physical violence from being clearly evident. Regarding the decomposition, it was found that in the 2nd and 3rd quartiles, 36.73% and 37.21% of the respective wage advantages of non-abused women are due to the Characteristics Effect (resulting from the observable factors considered in the proposed regressions), with the Structural Effect (defined by unobservable factors) not showing statistical significance. However, in the 1st quartile, it was identified that the observed wage difference can be attributed to both the Characteristics Effect and the Structural Effect.